Making Effective Decisions Through Analytics In Data-Driven Management - Sotvoldiev, Mirzoxidjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article analyzes the importance of the concept of Data-Driven Management in the modern business environment, its theoretical foundations and application in international practice. Companies are making strategic decisions faster and more effectively using Big Data, artificial intelligence (AI) and business analytics tools in the process of digital transformation. The article examines the impact of analytical management on efficiency using the example of large companies such as Amazon, Toyota, Coca-Cola. The prospects for introducing this approach in the economic environment of Uzbekistan are also analyzed.